Heart failure and right ventricular pacing – how to avoid the need for cardiac resynchronization therapy. (2nd January 2019) - Paton, Maria F.; Witte, Klaus K.
ABSTRACT: Introduction : Heart failure (HF) is a common finding in patients with pacemakers implanted for bradycardia, with cross-sectional and longitudinal studies contributing to the growing consensus that right ventricular pacing can cause adverse cardiac remodeling and left ventricular systolic dysfunction increasing the risk of hospitalization and death. An unselected approach using cardiac resynchronization therapy from the time of first implant in patients with heart block has produced equivocal results. Contemporary research has therefore begun to focus on the stratification of patients' risk of pacemaker-associated impairment to permit focused, personalized management. Areas covered : The present review will describe the incidence and relevance of HF in the pacemaker population and discuss current management options for such patients. Expert commentary : At present there are few contemporary data to guide the identification of patients with and at risk of pacemaker-associated cardiac remodeling and dysfunction. Emphasis must be placed on precise and personalized treatment approaches which currently remain under-investigated due to a number of challenges, for example, small sample sizes, limited clarity on programmed settings, and short follow-up periods.